Citizenship and identity : towards a new republic - Schwarzmantel, J. J. (John J.), 1947- (Routledge innovations in political theory, 2003)
Citizenship and Identity offers an analysis of contemporary politics and of the scepticism and apathy which characterise the political life of modern democracies. Starting from exploration of liberal-democracy and a critique of the fragmentation of contemporary politics, this book develops a republican perspective as an alternative framework for political institutions and civic participation.